Deficient Adipogenesis of Scleroderma Patient and Healthy African American Monocytes - Lee, Rebecca; Reese, Charles; Carmen-Lopez, Gustavo; Perry, Beth; Bonner, Michael; Zemskova, Marina; Wilson, Carole L.; Helke, Kristi L.; Silver, Richard M.; Hoffman, Stanley; Tourkina, Elena (Frontiers in Pharmacology, 2017)
Monocytes from systemic sclerosis (SSc, scleroderma) patients and healthy African Americans (AA) are deficient in the regulatory protein caveolin-1 leading to enhanced migration toward chemokines and fibrogenic differentiation. While dermal fibrosis is the hallmark of SSc, loss of subcutaneous adipose tissue is a lesser-known feature. To better understand the etiology of SSc and the predisposition of AA to SSc, we studied the adipogenic potential of SSc and healthy AA monocytes. The ability of SSc and healthy AA monocytes to differentiate into adipocyte-like cells (ALC) is inhibited compared to healthy Caucasian (C) monocytes. We validated that monocyte-derived ALCs are distinct from macrophages by flow cytometry and immunocytochemistry. Like their enhanced fibrogenic differentiation, their inhibited adipogenic differentiation is reversed by the caveolin-1 scaffolding domain peptide (CSD, a surrogate for caveolin-1). The altered differentiation of SSc and healthy AA monocytes is additionally regulated by peroxisome proliferator-activated receptor γ (PPARγ) which is also present at reduced levels in these cells. In vivo studies further support the importance of caveolin-1 and PPARγ in fibrogenesis and adipogenesis. In SSc patients, healthy AA, and mice treated systemically with bleomycin, adipocytes lose caveolin-1 and PPARγ and the subcutaneous adipose layer is diminished. CSD treatment of these mice leads to a reappearance of the caveolin-1+/ PPARγ+/ FABP4+ subcutaneous adipose layer. Moreover, many of these adipocytes are CD45+, suggesting they are monocyte derived. Tracing experiments with injected EGFP+ monocytes confirm that monocytes contribute to the repair of the adipose layer when it is damaged by bleomycin treatment. Our observations strongly suggest that caveolin-1 and PPARγ work together to maintain a balance between the fibrogenic and adipogenic differentiation of monocytes, that this balance is altered in SSc and in healthy AA, and that monocytes make a major contribution to the repair of the adipose layer.